Pediatric cirrhotic cardiomyopathy: Impact on liver transplant outcomes. Issue 6 (6th June 2018) - Junge, Norman; Junge, Claudia; Schröder, Julian; Pfister, Eva‐Doreen; Leiskau, Christoph; Hohmann, Dagmar; Beerbaum, Philipp; Baumann, Ulrich
Abstract : In adults, cirrhotic cardiomyopathy (CCM) has a significant incidence and impact on liver transplantation. For pediatric liver transplantation (pLT), data on liver‐induced cardiac changes are scarce, and in particular, the comparison between cirrhotic and noncirrhotic liver disease has not been investigated. We retrospectively evaluated cardiac changes associated with CCM by echocardiography and 12‐lead electrocardiogram in 198 pLT‐candidates (median age 4.1 years) 4.2 before and 12 months after pLT. Results were correlated with the stage of liver fibrosis and cholestasis before transplantation. The left ventricular end‐diastolic diameter (LVIDd) z score, left ventricular mass z score, and left ventricular mass index were significantly higher in cirrhotic patients (‐0.10 versus 0.98, P < 0.001; ‐1.55 versus ‐0.42, P = 0.001; 78.99 versus 125.64 g/m 2, P = 0.001, respectively) compared with children with noncirrhotic liver disease. Pathological z scores (>2SDS) for the LVIDd occurred more frequently in cirrhotic patients compared with patients with noncirrhotic liver disease (31/169 versus 1/29; P = 0.03) and were significantly associated with cholestasis. All observed cardiac changes were reversible 1 year after pLT. Pathological LVIDd z scores correlated highly with intensive care unit (ICU) stay (9.6 days versus 17.1 days, respectively, P = 0.002) but not with patient survival pre‐LT or post‐LT. In contrast to other studies, prolonged QTc time was not associated with liver cirrhosis in our patients. In conclusion, CCM‐associated cardiac changes in pLT candidates with cirrhotic liver disease are frequent, mild, and associated with cholestasis and reversible after pLT. They may impact peritransplant care and posttransplant hospitalization time. Further prospective evaluation is warranted. In particular, for QTc time prolongation etiological factors, possible protective effects of ursodeoxycholic acid treatment and the use as a screening parameter for CCM should be verified. Liver Transplantation 24 820–830 2018 AASLD.